ORGANIZATIONAL AND LEGAL FOUNDATIONS OF PUBLIC CONTROL IN UZBEKISTAN (World Bulletin of Management and Law, 2023)
In this article, the organizational and legal foundations of public control in the Republic of Uzbekistan are scientifically analyzed and the author's suggestions are developed.
Keywords: Public control; society; democracy; stage of development